Moderate Role of Oxytocin in the Pro-Ejaculatory Effect of the 5-HT1A Receptor Agonist 8-OH-DPAT. (1st January 2015) - de Jong, Trynke R.; Neumann, Inga D.
ABSTRACT: Introduction: The neurobiological control of ejaculation is not completely understood. Both serotonin (5-HT) and oxytocin (OXT) play a role in the control of male sexual parameters, putatively via overlapping neuronal networks. Aim: The aim of this study was to determine whether activation of 5-HT1A receptors (5-HT1A Rs) reduces the ejaculatory threshold via the direct activation of (OXT) neurons in the paraventricular hypothalamic nucleus (PVN). Methods: In experiment 1, male rats received acute bilateral infusions of the selective 5-HT1A R antagonist WAY-100635 (1 and 10 μg) or vehicle into the PVN, followed by acute subcutaneous (SC) injection of the potent 5-HT1 A R agonist 8-OH-DPAT (0.4 mg/kg) or saline. In experiment 2, male rats received acute bilateral infusions of 8-OH-DPAT (1 and 10 μg) or vehicle into the PVN. In experiment 3, male rats received acute intracerebroventricular (ICV) infusion of a selective OXT receptor antagonist (OXTR-A, 75 and 750 ng) followed by acute SC injection of 8-OH-DPAT (0.4 mg/kg) or saline. The effects of these drug treatments on sexual behavior were measured. Main Outcome Measures: Copulation latency, ejaculation latency, mount and intromission frequency, and ejaculation frequency of sexually experienced adult male Wistar rats during 30-minute sexual behavior tests with a receptive female were the main outcome measures. Results: Male sexual behavior was not affected by intra-PVN infusion of WAY-100635 or 8-OH-DPAT, or by ICV infusion of OXTR-A alone. However, the facilitation of ejaculation (reduced mount and intromission frequency and ejaculation latency) induced by systemic 8-OH-DPAT could be attenuated by either intra-PVN infusion of WAY-100635 or by ICV infusion of OXTR-A. Conclusions: Activation of OXT neurons plays a moderate role in the pro-ejaculatory effects of systemic 8-OH-DPAT, but extracellular 5-HT levels may influence the strength of the effects.